PREVALENSI DAN KARAKTERISTIK PASIEN MORBUS HANSEN TIPE MULTIBASILER YANG MENDAPAT TERAPI CLOFAZIMINE, OFLOXACIN, DAN MINOCYCLINE(COM)DI RUMAH SAKIT UMUM PUSAT SANGLAH PERIODE JANUARI – DESEMBER 2014 - Nuari, Hans; Darmada, I Gusti Ketut (E-Jurnal Medika Udayana; vol 4 no 10(2015):e-jurnal medika udayana, 2015)
PREVALENCE AND CHARACTERISTICS OF MULTIBACILLARY HANSEN’S DISEASEPATIENTS WITHCLOFAZIMINE, OFLOXACIN, AND MINOCYCLINE (COM) THERAPY INSANGLAH GENERAL HOSPITAL JANUARY– DECEMBER 2014 Hansen’s Disease (HD) or leprosy is a chronic disease which is still becoming a global health problem, including Indonesia, which ranks third in the world with the most prevalent new multibacillary (MB) cases.Lately, it has been found that many patients cannot be given Rifampicin as standard WHO therapy. Alternatively, they have been given Clofazimine, Ofloxacin and Minocycline (COM). This study was conducted to determine the prevalence of the HD, multibacillary (MB) HD, and MB HD with COM therapy and their characteristics in Sanglah Hospital at 2014. Hopefully this study could be useful as a reference to optimize the treatment of MH disease at health centers. The research is a descriptive study. Of the total 107 HD patients who visited Sanglah Hospital in 2014, the dominant sex was male and the dominant age was between aged 16-35 years.Of the total, 88.8% were patients with MB HD and 4.2% of MB patients treated with COM. Overall, Results of this study are expected to be used as a base for further descriptive or analytical research.
Keywords: Morbus Hansen; Multibacillary Leprosy; Clofazimine; Ofloxacin; Minocycline